2016
DOI: 10.14429/dsj.66.9783
|View full text |Cite
|
Sign up to set email alerts
|

Using Modelling and Simulation to Predict Dynamics of Converted Ground Vehicle

Abstract: In order to redesign and convert the passenger ground vehicle Land Rover defender 110 into military vehicle for different surveillance and reconnaissance missions it is necessary, prior to equipment integration, to assess its future dynamic response. For this purpose, the 19-degree of freedom multibody simulation model of the defender was developed using the software package MSC.ADAMS/Car. The simulation model was validated using the instrumented experimental vehicle for two scenarios namely bump test and doub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The Land Rover Defender 110 suspension model was initially developed by (Khettou et al, 2016) and, based on it, some modifications were made, shown in Figure 3 representing the vehicle in the roll plane in ADAMS/CAR. The model is represented by two masses connected by a suspension system.…”
Section: Adams/car Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The Land Rover Defender 110 suspension model was initially developed by (Khettou et al, 2016) and, based on it, some modifications were made, shown in Figure 3 representing the vehicle in the roll plane in ADAMS/CAR. The model is represented by two masses connected by a suspension system.…”
Section: Adams/car Modelmentioning
confidence: 99%
“…The Land Rover Defender 110 model was made in ADAMS/CAR software and the simulation model was validated using the instrumented experimental vehicle for two scenarios, namely, the bump test and the double lane change maneuver (Khettou et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The instrumented O prototype was equipped with different sensors to record dynamic parameters while the vehicle is running a double lane change maneuver. The experimental results are compared with those obtained for the baseline vehicle before the modification [7] in order to estimate degradation of dynamic characteristics. The effect of the mast elevation was also investigated by comparing experimental results of the converted vehicle MIP with telescopic mast at different heights.…”
Section: Ne Of the Main Activities Of The Military Technicalmentioning
confidence: 99%
“…ISO DLC is one of the standards for such tests. ADAMS /Car tool is capable of performing the simulations of closed-loop ISO DLC test and provides good results [6].…”
Section: Introductionmentioning
confidence: 99%